Absorption cross sections of 13C ethane and propane isotopologues in the 3 µm region. (December 2017) - Loh, Alain; Wolff, Marcus
Highlights: FTIR spectra of 13 C 12 CH6, 13 C2 H6 and 13 C 12 C2 H8 in the 3 µm region. Absorption peak positions of 13 C-isotopologues are shifted in comparison with ethane 12 C2 H6 and propane 12 C3 H8 . Results can be used to measure carbon isotope ratios of ethane and propane. Abstract: To the best of our knowledge, we present first-time measurements of the absorption cross sections of 13 C ethane and propane isotopologues in the spectral region around 3000 cm -1 . The spectra of 13 C 12 CH6, 13 C2 H6 and 13 C 12 C2 H8 have been recorded at approximate room temperature and atmospheric pressure for concentrations between 0.325% and 0.750% in nitrogen using an FTIR spectrometer with a resolution of 0.5 cm -1 . For calibration purposes an ethane and a propane spectrum each obtained with a natural isotopologue sample were compared to respective spectra from the Pacific Northwest National Laboratory (PNNL). The spectrum of 13 C 12 CH6 is shifted between 3.5 cm −1 and 3.8 cm -1 towards smaller wavenumbers compared to 12 C2 H6 . The peaks of 13 C2 H6 ethane were shifted between −4.4 cm -1 and −7.2 cm -1 relatively to the corresponding 12 C peaks. 13 C 12 C2 H8 shows a wavenumber shift of −2 cm −1 for the largest central peak at 2965.5 cm -1 and −6.5 cm -1 for the second largest peak at 2955 cm -1 . The newly determined cross sections will allow for the first time isotopologue-sensitive spectral analyses of ethane and propane in this spectral region and may be used for applications from atmospheric and planetary research to natural gas exploration.